Effect of endophytic diazotroph Enterobacter roggenkampii ED5 on nitrogen-metabolism-related microecology in the sugarcane rhizosphere at different nitrogen levels - Guo, Dao-Jun; Li, Dong-Ping; Yang, Bin; Verma, Krishan K.; Singh, Rajesh Kumar; Singh, Pratiksha; Khan, Qaisar; Sharma, Anjney; Qin, Ying; Zhang, Bao-Qing; Song, Xiu-Peng; Li, Yang-Rui (Frontiers in Microbiology, 2023)
Sugarcane is an important sugar and energy crop worldwide, requiring a large amount of nitrogen (N). However, excessive application of synthetic N fertilizer causes environmental pollution in farmland. Endophytic nitrogen-fixing bacteria (ENFB) provide N nutrition for plants through biological N fixation, thus reduce the need for chemical fertilizers. The present study investigated the effect of N-fixing endophytic strain Enterobacter roggenkampii ED5 on phytohormone indole-3-acetic acid (IAA), N metabolism enzyme activities, microbial community compositions, and N cycle genes in sugarcane rhizosphere soil at different N levels. Three levels of 15N-urea, low N (0 kg/ha), medium N (150 kg/ha), and high N (300 kg/ha) were applied. The results showed that, after inoculating strain ED5, the IAA content in sugarcane leaves was significantly increased by 68.82% under low N condition at the seedling stage (60 days). The nitrate reductase (NR) activity showed a downward trend. However, the glutamine synthase (GS) and NADH-glutamate dehydrogenase (NADH-GDH) activities were significantly enhanced compared to the control under high N conditions, and the GS and NR genes had the highest expression at 180 and 120 days respectively at low N level. The total N content in roots, stems, and leaves of sugarcane were higher than the control. The 15N atom % excess of sugarcane decreased significantly under medium N condition, indicating that medium N level were conducive to N fixation of strain ED5. Metagenome analysis of sugarcane rhizosphere soil exhibited that the abundance of N metabolizing microbial richness was increased under low and high N conditions after inoculation of strain ED5 at the genus level, while it was increased at the phylum level only under low N condition. The LefSe (LDA>2, p<0.05) found that the N metabolism-related differential microorganisms under high N condition were more than those under medium and low N conditions. It was also shown that the abundance of nifDHK genes were significantly increased after inoculation of ED5 at medium N level, and other N cycle genes had high abundance at high N after inoculation of strain ED5. The results of this study provided a scientific reference for the N fertilization in actual sugarcane production.